Essential fatty acid deficiency in freshwater fish: the effects of linoleic, alpha-linolenic, gamma-linolenic and stearidonic acids on the metabolism of [1-14C]18:3n-3 in a carp cell culture model - Tocher, Douglas R; Dick, James R (Springer, 2000)
The desaturation of [1-14C]18:3n-3 to 20:5n-3 and 22:6n-3 is enhanced in an essential fatty acid deficient cell line (EPC-EFAD) in comparison with the parent cell line (EPC) from carp. In the present study, the effects of competing, unlabeled C18 polyunsaturated fatty acids (PUFA), linoleic (18:2n-6), α-linolenic (18:3n-3), γ-linolenic (18:3n-6) and stearidonic (18:4n-3) acids, on the metabolism of [1-14C]18:3n-3 were investigated in EPC-EFAD cells in comparison with EPC cells. The incorporation of [1-14C]18:3n-3 in both cell lines was significantly reduced by competing C18 PUFA, with the rank order being 18:4n-3 > 18:3n-3 = 18:2n-6 > 18:3n-6. In the absence of competing PUFA, radioactivity from [1-14C]18:3n-3 in EPC cells was predominantly recovered in phosphatidylethanolamine followed by phosphatidylcholine. This pattern was unaffected by competing n-6PUFA, but n-3PUFA reversed this pattern as did essential fatty acid deficiency in the presence of all competing PUFA. The altered lipid class distribution was most pronounced in cells supplementedwith 18:4n-3. Competing C18 PUFA significantly decreased the proportions of radioactivity recovered in 22:6n-3, pentaene and tetraene products, with the proportions of radioactivity recovered in 18:3n-3 and 20:3n-3 increased, in both cell lines. However, the inhibitory effect of competing C18 PUFA on the desaturation of [1-14C]18:3n-3 was significantly greater in EPC-EFAD cells. The magnitude of the inhibitory effects of C18 PUFA on [1-14C]18:3n-3 desaturation was dependent upon the specific fatty acid with the rank order being 18:4n-3 >18:3n-3 >18:2n-6, with 18:3n-6 having little inhibitory effect on the metabolism of [1-14C]18:3n-3 in EPC cells. The differential effects of the C18 PUFA on [1-14C]18:3n-3 metabolism were consistent with mass competition in combination with increased desaturation activity in EPC-EFAD cells and the known substrate fatty acid specificities of desaturase enzymes. However, the mechanism underpinning the greater efficacy with which ...